The economic gains of closing the employment gender gap: Evidence from Morocco - Olivier Bargain; Maria C. Lo Bue (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
The present paper sheds new light on the growth implications of gender inequalities in the Moroccan labour market. We confront two different approaches. The first one is based on firm data to estimate gender complementarity in production and uses this information for simulations based on a simple macroeconomic model. The second relies on country panel variation to relate growth to the relative employment of women and, also, suggest simulations for Morocco. Both approaches lead to similar conclusions regarding the potential economic gains from increased female participation in this country. This paper is one of the rare attempts to elicit the growth potential of a reduction in the employment gap in a low-income country.
Keywords: E23; J16; J24; O41; 330; Morocco; female labour force participation; gender employment gap; growth; aggregate production function; constant elasticity of substitution; firm data